PKM Bengkel Motor Rumahan - Djami, Jolis Joskar Anderias; Toineno, Melianus (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2019)
This partnership or community service activity was implemented in "Bengkel Motor Nager" with the aim of assisting and realizing the knowledge and skills related to the construction of motorcycle engines, the working principle of motor machines, engine Fittings, electrical motorcycles, Unloading and tuning of machines, and on the motorcycle engines, which are specific focused on fuel measurements and compression ratios on the engine and camshaft; and the fulfillment of repair equipment to support the profession and business partners. The implementation method applied is to perform the Focus Group Discussion (FGD) with the partner; contact and elicit mechanical experts; Schedule of Trainings agreed together between the proposal, partners and trainers, the implementation of training, namely the introduction of theories and practices; procurement of repair equipment for partners. The results that have been achieved are the partners have the knowledge and skills needed by the partner, specifically everything related to motor machines and partners also have the repair equipment that supports the profession and business partners for the term long.